Pelaksanaan Peraturan Daerah N0.7 Tahun 2003 - Putri Adelina; Ahmatnijar Ahmatnijar; Dermina Dalimunthe (IAIN Padangsidimpuan, 2021)
Implementation of Regional Regulation Number 7 of 2003 concerning Prevention and Eradication of Community Diseases in Gunung Tua Tonga Village, Panyabungan City District.The background of this research is the implementation of Regional Regulation No. 7 of 2003 concerning Prevention and Eradication of Community Diseases in Gunung Tua Tonga Village, Panyabungan City District. Which of course has an impact on the lack of public understanding of the Regional Regulation Number 7 of 2003 concerning the Prevention and Eradication of Community Diseases, it causes more people to consume narcotics and distribute liquor.The formulation of the problem of this research is how the implementation of regional regulation Number 7 of 2003 concerning the prevention and eradication of community diseases in Gunung Tua Tonga Village, Panyabungan Subdistrict, the city and the factors that become inhibitors and supporters in the implementation of the region Number 7 of 2003 concerning the Prevention and Eradication of Community Diseases in Gunung Tua Tonga Village, Panyabungan City DistrictBy using this field research, the location is in Gunung Tua Tonga Village, Panyabungan District, Kota. so to find out the results or the truth of the problems in this study, researchers used data collection instruments by means of interviews and documentation. Meanwhile, to manage the data is done by identification, category, analysis, and conclusion.After doing the research, the results showed that in the implementation of regional regulation number 7 of 2003 concerning Prevention and Eradication of Community Diseases, it had been implemented although it was not yet effective because there were still found in the field using narcotics or liquor in Gunung Tua Tonga Village, Panyabungan City